Effects of Fertilization Quantities on the Development of Wine Varieties of Grapes - Malikov Azim Nematovich; Abdullayeva Barno Atabekovna Sobirovich; Parmonova Adiba Davlat qizi (International Journal on Economics, Finance and Sustainable Development, 2021)
The article examines the effect of fertilizer amounts on the development of fruiting branches of grape wine varieties. The experiments were performed on five variants in four varieties. In all of these varieties the highest result was recorded in the fourth variant (N140P110K80 kg pure). Even when fertilizer was applied in large quantities, it had a negative effect on the biological properties of the varieties.